Worldwide trends in incidence in occupational allergy and asthma. Issue 2 (April 2016) - Stocks, Susan J.; Bensefa-Colas, Lynda; Berk, Sarah F.
Abstract : Purpose of review: Recent improvements in the methods for analyzing trends in occupational health surveillance and the prospect of future improvements in the collecting and sharing of electronic data alongside increasing availability of linked datasets make this a good time to review the existing literature on trends in occupational allergy and asthma (OAA). Recent findings: There is a notable lack of reports of recent trends in OAA in the academic literature and much of the published work comes from European countries. The incidence of OAA appears to be declining based on physician-reporting or recognized compensation claims for the countries with published data. However, we need to be cautious in interpreting this as a decline in the 'true' incidence of OAA. Few of the studies adjusted appropriately for changes in the population at risk and one of the most robust study designs showed no change in the incidence of allergic contact dermatitis in contrast to the other studies. Summary: Many existing datasets have the potential to be used to examine trends, and studies from Canada show the potential of using linked databases for surveillance. We hope that this review will encourage improvements in the analysis, and more dissemination, of trends.